ASPEK SUPRAGSEMENTAL SEBAGAI PENDUKUNG KONSTRUKSI TEMA-REMA DALAM BAHASA JAWA BANYUMAS - Restu Sukesti (Balai Bahasa Sulawesi Utara, 2017)
Theme-rheme construction is a part of the universality language in the world. The most important aspect as thesupporter of theme-rheme construction is suprasegmental aspect, which is intonation role. With that intonation role,theme-rheme unsure and variation can be determined. In a theme-rheme construction research in Javanese-Banyumas,based on intonation role research, found that there is unique characteristic of theme, rheme, and supplement unsure. It isfound that there are six theme-rheme construction roles in Javanese-Banyumas, based on the intonation role as well.Moreover, five of those six roles can change into another role because of intonation role changing. Thus, suprasegmentalaspect has huge influence to the theme-rheme construction. AbstrakKonstruksi tema-rema merupakan salah satu ciri keuniversalan bahasa-bahasa di dunia. Aspek yangterpenting sebagai pendukung konstruksi tema-rema ialah aspek suprasegmental, yaitu pola intonasi.Dengan pola intonasi tersebut, unsur-unsur dan variasi konstruksi tema-rema dapat ditentukan. Dalamkajian konstruksi tema-rema dalam bahasa Jawa Banyumas, berdasarkan kajian pola intonasinya,ditemukan kekhasan unsur tema, rema, dan suplemen. Berdasarkan pola intonasi itu pula, dalambahasa Jawa Banyumas ditemukan enam pola konstruksi tema-rema. Lima di antara enam pola tersebutdapat berubah menjadi pola lain karena perubahan pola intonasinya. Dengan demikian, aspeksuprasegmental sangat berpengaruh terhadap konstruksi tema-rema.